Relationship of the Mean Glandular Dose with Compressed Breast Thickness in Digital Mammography - Khadka, Samjhana; Jha, Anamika; Chaudhary, Ranjit Kumar; Shrestha, Shanta Lall (Nepalese Journal of Radiology, 2020)
Introduction: Mammography is one of the most commonly performed radiological investigations for evaluation of breast cancer. As it involves ionizing radiation, there remains a risk of radiation induced cancer. In this study, we evaluated compressed breast thickness (CBT) and mean glandular dose (MGD) during routine mammography. Methods: This prospective study was performed in the Department of Radiology and Imaging of TUTH. Data of 500 consecutive patients who underwent mammography over a period of 4 months (June 2018 to September 2018) was collected. The age, CBT and MGD were recorded. Pearson correlation and paired-t tests were performed. Results: Most of the patients belonged to 41-50 years age group. MGD was significantly higher in patients with increased CBT. The CBT and MGD was higher in MLO view compared to CC views. The mean value of total MGD for four views was 5.1±1.4 mGy. There was significant positive correlation (r= 0.517) between CBT and MGD with increase in MGD with increase in CBT. Conclusions: The MGD and dose equivalent in our routine mammography is within the recommended limits. MGD increases with increasing CBT and vice-versa. Hence, decreasing the thickness of compressed breast, can decrease the amount of radiation absorbed by the glandular tissue of the breast.